EVALUASI TINGKAT KEBERHASILAN PELAKSANAAN PROGRAM INSEMINASI BUATAN SAPI PERANAKAN FRISIEN HOLSTEIN (PFH) DI DESA SEMEN KECAMATAN GANDUSARI KABUPATEN BLITAR - Yuli Masfufah; Edya Moelia Moeis; Anang Widigdyo (AVES: Jurnal Ilmu Peternakan, 2018)
The main objective of this study was to evaluate the success rate of Artificial Insemination (IB) in the Village of Semen Gandusari District, Blitar Regency. This research method is done in 2 ways, namely, descriptive and quantitative analytical. Quantitative data types are data in the form of numbers including: Number of IB services, number of females in IB, all pregnant females IB results, number of pregnant females first IB results, Data Realization of Artificial Insemination activities and recapitulation data on Artificial Insemination births, Number of Days / Months between one birth and the next, the number of farmers applying the IB program. The type of data used is primary and secondary data. The results of the research in the form of primary and secondary data obtained qualitatively are processed descriptively, while the quantitative ones are processed statistically with an average value then interpreted according to the statistics. The results that have been obtained evaluating the success rate of IBs in the working area of Semen KUD, especially Semen village, are as follows: Non Return Rate (NRR) 38.42 ± 32.91%, Conception Rate (CR) 38.42 ± 32.91%, Service Per Conception (S / C) 2.23 ± 0.95 times, 433.2 ± 57.3 days of Calving Interval (CI). It can be concluded that dairy cows in the Semen village pretty good value even though not optimal. Suggestions that need to be carried out further research on factors that influence the success of artificial insemination programs (IB).